Fragments of a Haunted Mind: Involuntary Memory and Unreliable Narration in A Pale View of Hills (International Journal of Food and Nutritional Sciences, 2022)
With an emphasis on Etsuko’s disjointed and untrustworthy narration, this paper explores the function of involuntary recollection in Kazuo Ishiguro’s A Pale View of Hills. Based on Ansgar Nünning’s paradigm for narrative unreliability